2012
DOI: 10.1007/s00276-012-1050-8
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of different histological layers of the pachygyria/agyria cortex using diffusion tensor MR imaging

Abstract: DTI is a useful tool for identifying gross histological features of pachygyria-agyria complex. Superficial layer and thickened fourth layer demonstrate high anisotropy. Identification of anisotropy in the superficial layer has not been described in previous reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The radial glias retract their ventricular and pial attachments and differentiate into astrocytes as the brain matures normally, with corresponding decrease in the cortical FA value. The radially oriented structure within the cortex demonstrated in this case may represent remains of radial glia or persistent radial orientation of neurons arrested in the migration process [7]. …”
mentioning
confidence: 99%
“…The radial glias retract their ventricular and pial attachments and differentiate into astrocytes as the brain matures normally, with corresponding decrease in the cortical FA value. The radially oriented structure within the cortex demonstrated in this case may represent remains of radial glia or persistent radial orientation of neurons arrested in the migration process [7]. …”
mentioning
confidence: 99%
“…Previous 3D tractography studies identified these as separate, thick, brush-like fibers. 11,12 However, our case did not demonstrate similar fiber anatomy. We also identified a small fiber bundle across the small posterior interhemispheric fissure dorsal to the fused midline mass.…”
Section: Discussionmentioning
confidence: 64%